Vloga glagolske perifraze haber de + nedoločnik v časovni strukturi romana Sto let samote - Markič, Jasmina (Ars et humanitas, 2012)
This article analyzes some temporal and aspectual values (past future, imminence of an event) intermingled with modal values (epistemic values of obligation, necessity and probability) of the Spanish verbal periphrasis haber de + infinitive which convey very special stylistic values and meanings in Gabriel García Márquez's novel One Hundred Years of Solitude. Haber de + infinitive (in the imperfect tense of the indicative: había de + infinitive) introduces the first sentence and activates the events in the novel, giving them a particular temporal and spatial frame. Through the narrative techniquesof flashback and flash forward -present in this novel, in which the dominant theme is time and the inevitable repetition of history in Macondo - the above-mentioned verbal periphrasis plays an important role in signalling events that can be neither avoided nor stopped. With its strong expressive force, and due to its basic temporal and modal meanings, the verbal periphrasis haber de + infinitive has a premonitory function in the novel: it predicts fatal events in the lives of the inhabitants of Macondo - inhabitants who are controlled by their pasts and the complexity of time - and in the history of the town which seems to be doomed and predetermined from its very existence.
Keywords: Spanish; španščina; verbal periphrasis; verb; spanish language; glagol; modalnost; temporality; čas; modality